Method and assembly for copper-to-copper direct bonding
Patent Information
- Application Number
- JP2023554044
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-03-06
- Filing Date
- 2022-03-04
- Publication Date
- 2025-03-12
- Estimated Expiration
- 2042-03-04
AI Technical Summary
Existing copper-copper bonding techniques in semiconductor manufacturing face challenges with bond formation, bond strength, and ductility, particularly in miniaturized applications, and require higher annealing temperatures that can damage temperature-sensitive devices.
A method involving electrochemical copper deposition followed by an annealing process at low temperatures (below 200°C) to transform copper grains from a small size to larger grains that penetrate through the bonding interface, eliminating the need for additional surface smoothing and reducing grain growth until the bonding process, thereby enhancing bond strength and electromigration performance.
This method improves bond formation, bond strength, and electromigration while maintaining the integrity of temperature-sensitive devices by ensuring grain growth occurs during bonding, eliminating detectable interfaces and enhancing the reliability of copper-copper junctions.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a novel method for copper-copper direct bonding in the manufacture of assemblies, in particular in the manufacture of assemblies for interconnecting conductive copper structures in wafer-to-wafer, die-to-wafer or die-to-die processes in the semiconductor industry. [Background technology]
[0002] Modern electronics manufacturers are faced with the demand for ever-increasing miniaturization and must pursue the trend for ever-higher density electrical interconnections. Heterogeneous integration is considered a key technology to meet current and future demands in the semiconductor industry. Heterogeneous integration involves the integration of separately manufactured components into assemblies, thus increasing functionality and improving operational characteristics. Copper is the main interconnect material for the individual components and their packaging. In this context, 3D stacking of components within a package allows for increased interconnect density, reduced form factors, and increased efficiency.
[0003] The joining of individual components is required in various processes such as wafer-to-wafer, die-to-wafer and die-to-die processes. Traditional joining techniques include copper bumps and copper pillars combined with solder materials, which are widely used in current packaging applications. Such copper pillars are usually produced by electrolytic copper deposition. However, typical processes usually suffer from relatively large non-uniformities in the range of several micrometers, especially in terms of coplanarity and total thickness variations. Solder materials, usually tin or tin-silver alloys, can compensate these non-uniformities to some extent.
[0004] To increase interconnect density, the distance between copper bump pillars needs to be reduced. Conventional soldering techniques may not be suitable for fine-pitch applications because the solder material may protrude from the structure during bonding, resulting in electrical shorts. These issues may be overcome by directly forming copper-copper interconnects, omitting the conventional solder cap in microbumps and reducing the pitch between bumps to values clearly below 20 μm. Therefore, several attempts have been proposed to improve the bond formation, including surface activation by ion beam, chemical mechanical polishing (CMP), surface passivation by alloying copper with other elements, metallic and organic finishes, and structural design.
[0005] Many applications involve temperature-sensitive devices, requiring alternative low-temperature joining techniques. Hybrid joining, which involves copper-copper direct interconnects encapsulated in silicon dioxide, has been proposed as a promising alternative.
[0006] WO2020046677A1 describes a hybrid bonding process in which the structure provides a vertical stack of conductive layers encapsulated by a surrounding dielectric, the dielectric having a shape and thermal expansion function designed to expand the stack vertically over a precise recess distance at low temperatures to create a copper-copper direct bond at the bonding interface without the use of solder or adhesive. In the first step, the oxide surfaces of the inorganic dielectrics are directly bonded, and in the second step, the metals encapsulated by the surrounding dielectric are directly bonded. The copper-copper bond is based on the surface diffusion of copper atoms that diffuse to the interface to form a permanent bond.
[0007] US9881888B2 discloses a Cu-Cu interconnect structure in which the body of a copper post has a coarse average grain size and the outer surface of the copper post has a fine average grain size, and then a portion of the outer surface of the copper post is brought into contact with another copper surface, and pressure and heat are applied to achieve copper-to-copper fusion.
[0008] Chuan Seng Tan: "Recent progress in copper-based wafer bonding for 3-D ICs application", 2008 INTERNATIONAL CONFERENCE ON ELECTRONIC MATERIALS AND PACKAGING: (EMAP 2008) IEEE, October 22, 2008 (2008-10-22), pp. 45-48, describes thermocompression bonding of copper metal (also known as diffusion bonding) and its use in 3D stacking of ICs, in which a blanket Cu film deposited on two oxide wafers fuses to form a homogeneous layer under suitable bonding conditions, i.e., temperature range 300-400°C and contact pressure 226 kPa.
[0009] However, the aforementioned techniques cannot meet the future demands of increasing miniaturization. Improved bond formation and bond strength, as well as improved ductility, are still required. Many applications involve temperature-sensitive devices, so low annealing temperatures are still required to avoid component damage and loss of electrical conductivity. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] WO2020046677A1 [Patent Document 2] US9881888B2 [Patent Document 3] EP3286358B1 [Non-patent literature]
[0011] [Non-Patent Document 1] Chuan Seng Tan: "Recent progress in copper-based wafer bonding for 3-D ICs application", 2008 INTERNATIONAL CONFERENCE ON ELECTRONIC MATERIALS AND PACKAGING: (EMAP 2008) IEEE, October 22, 2008 (2008-10-22), pp. 45-48 Summary of the Invention [Problem to be solved by the invention]
[0012] It is therefore an object of the present invention to overcome the shortcomings of the prior art and to provide a means for improving bond formation and bond strength.
[0013] A further object of the present invention is to provide a means for lowering the annealing temperature during copper-copper direct bonding.
[0014] Yet another object of the present invention is to reduce the number of process steps and to provide an improved bonding surface for the deposits being bonded.
[0015] It is yet another object of the present invention to improve electromigration within the formed copper-copper joints. [Means for solving the problem]
[0016] These objectives are achieved by the present invention.
[0017] In one embodiment of the present invention, a method for copper-copper direct bonding comprises: a) providing a first substrate comprising a first pure copper deposit having a bonding surface, preferably the first substrate being a wafer or die-like substrate; b) providing a second substrate comprising a second pure copper deposit having a bonding surface, preferably the second substrate being a wafer-like substrate or a die-like substrate; c) connecting a mating surface of the first deposit with a mating surface of the second deposit to obtain a connected deposit; d) transforming the first and second stacks of the connected stack into a connected and transformed stack; Including, - the first and second deposits are formed by a deposition electrochemical copper deposition process and have copper grains with a smaller grain size than the grain size after conversion by step d), preferably the grain size is nanocrystalline, more preferably the grain size is on average less than 0.8 μm, more preferably between 0.01 μm and 0.70 μm, most preferably between 0.01 μm and 0.3 μm, the connected and converted deposit has grains with a size larger than the grain size before the conversion in step d), preferably with an average grain size of 0.1 μm to 13 μm, more preferably 1 to 10 μm, Step d) is carried out by applying an annealing step having an annealing temperature below 200°C, preferably between 150°C and 200°C.
[0018] In another aspect of the invention, the assembly comprises: i) - connecting a joining surface of a first pure copper deposit of a first substrate with a joining surface of a second pure copper deposit of a second substrate; - transforming the first and second piles of the connected pile into a connected and transformed pile; and a connected and converted deposit obtained by the first deposit and the second deposit are formed by a deposition electrochemical copper deposition process and have copper grains with smaller grain size compared to the copper grains of the connected and converted deposits with larger grain size after applying an annealing step with an annealing temperature below 200 °C, preferably between 150 °C and 200 °C, preferably the grains of the first deposit extend through the joining surface of the first and second deposits into the second deposit and vice versa.
[0019] In yet another aspect of the invention, the device comprises: i) - connecting a joining surface of a first pure copper deposit of a first substrate with a joining surface of a second pure copper deposit of a second substrate; - transforming the first and second piles of the connected pile into a connected and transformed pile; and a connected and converted deposit obtained by the first and second deposits are formed by a deposition electrochemical copper deposition process and have copper grains with smaller grain sizes compared to the copper grains of the connected and converted deposits with larger grain sizes after applying an annealing step with an annealing temperature of less than or equal to 200 ° C, preferably between 150 ° C and 200 ° C, The first and second substrates are part of a microelectronic device, preferably a wafer or a die.
[0020] In particular, the present invention avoids additional method steps, such as modifying the bonding surface structure prior to the bonding process to prepare a smooth bonding surface, and reducing the bonding temperature, such as in surface activated bonding using ultra-high vacuum (UHV) conditions and the Cu nanorod method using copper nanorod arrays as a bonding interlayer.
[0021] Since the complicated process of inserting specific structures in the joining surface is avoided, the present invention helps to further smooth the joining surface and reduce the need for a CMP step to prepare a uniform / smooth surface with very low surface roughness. In this context, a smooth surface means a surface roughness Ra of less than 300 nm, preferably less than 50 nm. Preferably, the surface roughness Ra is in the range of 5 nm to 200 nm, more preferably in the range of 10 nm to 50 nm, even more preferably in the range of 10 nm to 40 nm, and / or the deviation of the average thickness of the deposit is 5 to 10%.
[0022] Since the metal deposit was formed by an electrochemical copper deposition process, the bonding surface of the metal deposit is already very smooth. However, if a surface roughness Ra of less than 10 nm is required, a short CMP step may be useful and / or CMP is used as a short cleaning step to prepare the bonding surface of the substrate. In particular, short CMP is used to remove, for example, copper oxide and / or fine dust-like particles.
[0023] Furthermore, bond strength, bond formation, and electromigration performance are greatly improved because no distinct interface (the area where the bonding surfaces touch each other) is detectable after the conversion process. That is, the smooth surface of the original bonding surface (which formed a distinct interface before conversion) is no longer distinct or nearly undetectable after conversion. Rather, the original bonding surfaces are blurred and fused (at least partially interdigitated) as the grains of the deposit have grown through the surface from both sides to the other side.
[0024] Further aspects of the invention can be seen from the dependent claims or the following description.
[0025] The features will become apparent to those skilled in the art from the detailed description of the exemplary embodiments taken in conjunction with the accompanying drawings. [Brief description of the drawings]
[0026] [Figure 1] FIG. 1 illustrates the formation of a copper-copper direct bond. [Diagram 2] FIG. 13 shows a simulation of the conversion step d). [Diagram 3] FIG. 1 shows normalized grain size of copper alloy and pure copper deposits. [Figure 4] FIB SEM micrographs of pure copper deposited with different time and temperature parameters. [Figure 5a] 1 is a FIB SEM micrograph of the formation of a copper-copper direct bond between two wafers according to the present invention. [Figure 5b]1 is a FIB SEM micrograph of the formation of a copper-copper direct bond between two wafers according to the present invention. [Figure 5c] 1 is a FIB SEM micrograph of the formation of a copper-copper direct bond between two wafers according to the present invention. [Figure 6a] 1 is a FIB SEM micrograph of the formation of a copper-copper direct bond between two wafers according to a comparative example. [Figure 6b] 1 is a FIB SEM micrograph of the formation of a copper-copper direct bond between two wafers according to a comparative example. [Figure 6c] 1 is a FIB SEM micrograph of the formation of a copper-copper direct bond between two wafers according to a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] Reference will now be made in detail to the embodiments illustrated in the accompanying drawings. The advantages and features of the exemplary embodiments, as well as the manner of carrying out the same, will be described with reference to the accompanying drawings. In the drawings, the same reference numerals represent the same elements, and redundant description will be omitted. As used herein, the term "and / or" includes any and all combinations of one or more of the listed items associated with the term. Furthermore, the use of "may" in describing an embodiment of the present invention refers to "one or more embodiments of the present invention."
[0028] In the following description of embodiments of the present invention, singular terms may include plural unless the context clearly indicates otherwise. For example, when "deposit" is used in the following description, "deposits" are included. Furthermore, "on average" means that the value is an average of multiple values, and that a particular value may be higher or lower than the average value.
[0029] In the context of the present invention, pure copper denotes the purity of the copper deposit, which means that the copper content of the copper deposit is 99% by weight, preferably 99.9% by weight, more preferably 99.99% by weight. That is to say, each pure copper deposit means a copper deposit with a copper content of at least 99% by weight, preferably at least 99.9% by weight, more preferably at least 99.99% by weight. In particular, pure copper does not contain any alloy metals or organic residues in the aforementioned percentages by weight.
[0030] The first and second substrates may be part of an assembly after carrying out the method of the invention and / or may be part of a microelectronic device as a wafer-like or die-like substrate processed according to the invention. The connection of the joining surfaces according to the method of the invention may be a step in a wafer-to-wafer (W2W) process, a die-to-wafer (D2W) process or a die-to-die (D2D) process.
[0031] The first and second substrates may further comprise, independently of each other, additional metal deposits with different metal compositions, for example copper alloys, forming a vertical stack. The additional metal deposits of the first substrate are connected with the first deposits, and the additional metal deposits of the second substrate are connected with the second deposits. Each additional metal deposit has a respective coefficient of thermal expansion (COE). The first and second deposits as well as the additional metal deposits may be encapsulated by a dielectric material. The manufacture of these substrates is in principle known to the person skilled in the art.
[0032] The first substrate may further comprise a first non-conductive material, e.g. a dielectric material having a bonding surface and at least partially encapsulating the first deposit, and the second substrate may further comprise a second non-conductive material, e.g. a dielectric material having a bonding surface and at least partially encapsulating the second deposit, where the bonding surfaces of the first and second deposits are below or at the same height as the bonding surfaces of the first and second non-conductive materials.
[0033] The first deposit on the first substrate and the second deposit on the second substrate may be independently selected from the group consisting of a via, a bump, a pillar and / or a pad.
[0034] While the prior art has focused on optimizing CMP, oxide-oxide bonding process steps connecting the dielectric material encapsulating the copper vias, and improving the diffusion of copper atoms at the copper surface between the bonding surfaces of the substrates being bonded, the present invention deals with the different aspects of the copper deposit before and after bonding in terms of copper grain size and purity of the copper deposit for the electrolytic deposition process, and improved conditions for the subsequent copper-copper bonding process in the hybrid bonding process sequence related to time and annealing temperature.
[0035] The invention is based on two main findings: first, that the crystal structure of the deposit after plating should be preserved and not altered until the copper-copper bonding process is started, and second, that the grain growth initiated within the copper-copper bonding process (mainly step d)) leads to grains penetrating the original uniform bonding surface of one deposit into the other deposit, which causes the original uniform bonding surface to disappear or to disappear mainly. In this connected and transformed deposit, the bonding strength is improved and the reliability of the connected (and transformed) deposit is greatly improved.
[0036] Own experiments have shown that the timescale for maintaining small grains at room temperature depends on the electrolytic copper process and can be controlled by suitable adjustment of the deposition parameters. In particular, the purity of the copper deposit and the temperature used for copper deposition allow a microstructure similar to the initial morphology to be maintained for a long time at room temperature. As a result, timescales should be sufficient for introduction into the process sequence of industrial hybrid joints. Without being bound by theory, grain growth on the interface (joining surface of the deposits) is, according to the invention, preferably initiated from the initial structure during the transformation upon application of a thermal load, for example relaxed by an annealing step.
[0037] In particular, it has been found that the annealing temperature of copper electrolytically deposited films can be affected depending on the codeposited impurities, particularly depending on the organic plating additives and plating conditions, and that the annealing temperature can be reduced taking into account the requirements of the bonding process flow and the resulting package quality.
[0038] The conversion step of the present invention is carried out in particular after an electrochemical copper deposition step for preparing a pure copper deposit, in particular after preparing conductive copper structures as vias on a substrate. Preferably, the conversion step is carried out after the electrochemical copper deposition step without further heat treatment, for example without an annealing step before applying the present invention. That is to say, the copper deposit is only exposed to ambient (room) temperature or below after the electrolytic process.
[0039] Preferably, the period from steps a) and b) until steps c) and / or d) are carried out does not exceed 3 weeks, more preferably does not exceed 120 hours, and even more preferably does not exceed 72 hours. Preferably, the substrate from steps a) and b) is stored at room temperature (in the range of 18°C to 25°C), preferably below 25°C, more preferably in the range of 5°C to 25°C, during the above period.
[0040] According to the invention, step c) - connecting the joining surfaces of the first deposit with the joining surfaces of the second deposit to obtain a connected deposit - is understood to mean bringing at least parts of the joining surfaces of the deposits of substrates into direct contact with each other, for example by arranging the substrates face to face and clamping them together on a bonding chuck.
[0041] When the first substrate comprises a first non-conductive material having a bonding surface and at least partially encapsulating the first deposit, and the second substrate further comprises a second non-conductive material having a bonding surface and at least partially encapsulating the second deposit, and the bonding surfaces of the first and second deposits are below (or partially below) or at the same height as the bonding surfaces of the first and second non-conductive materials, step c) comprises directly contacting at least a portion of the bonding surfaces of the non-conductive materials of the substrates with each other, for example by arranging the substrates face to face and clamping the substrates together on a bonding chuck. This connection can be achieved by pressing the first and second bonding surfaces of the non-conductive materials of the first and second substrates with a certain pressure. In this embodiment, the bonding surfaces of the first and second deposits of the first and second substrates are brought into contact with each other simultaneously with the bonding surfaces of the non-conductive materials, or are at least partially brought into contact after the bonding surfaces of the non-conductive materials have been bonded.
[0042] The pressure may be applied with a contact force of 1-5,000 N. In one embodiment, the contact force in step c) may be 3,500-4,500 N when the substrates are in full contact.
[0043] Step c) can be carried out without heating to a higher temperature, in particular at a temperature below 100° C., preferably at room temperature (preferably in the range from 18 to 25° C.).
[0044] The method according to the invention can be used in the manufacture of assemblies and / or devices in packaging applications.
[0045] The present invention makes it possible to improve the bond formation and bond strength of the copper deposit between the substrates being joined.
[0046] Grain growth at the bond interface (the area where the bond surfaces of the first and second deposits contact each other) has been achieved. Grain growth is very important for good and sufficient copper-copper bond formation and high reliability. The growth of grain size (the small grains that electrochemical deposition provides as starting point) is prevented or at least delayed or slowed down until the conversion process begins.
[0047] The copper grains of the first and second deposits after the electrochemical copper deposition step are preferably nanocrystalline, meaning that they have a grain size of less than 1 μm, more preferably a grain size of less than 0.8 μm on average, more preferably between 0.01 μm and 0.70 μm, and most preferably between 0.01 and 0.3 μm.
[0048] The copper grains of the connected and converted deposit have an average grain size of 0.1 μm to 13 μm, more preferably 1 to 10 μm, and most preferably 1 μm to 5 μm. In principle, the grain size of the copper grains of the connected and converted deposit is limited only by the thickness of the connected and converted deposit (the length of the area of the first and second deposits combined).
[0049] After the connecting step c), the grain size of the first deposit and the grain size of the second deposit become part of the connected deposit, and during the converting step d), the grain size grows and the formed copper grains spread through the joint surface (also called the interface where both joint surfaces are in contact with each other) of the first deposit and the second deposit into the respective other deposit. That is, the grains of the first deposit spread into the second deposit and vice versa. In this context, "vice versa" means that the grain size of the second deposit also grows and the formed copper grains of the second deposit spread through the joint surface (also called the interface where both joint surfaces are in contact with each other) of the second deposit into the first deposit. As a result, the joint surface (forming the interface) with a uniform tendency of the deposits, which was connected before the conversion, disappears and the copper grains extend through (the area of) the connected and converted deposit, preferably through at least 75% or more of (the area of) the connected and converted deposit, more preferably through the entire (area of) the connected and converted deposit. For example, if the area of connected and converted deposits has a maximum length of 5 μm (the length of the area of the first deposit and the second deposit combined), the copper grains may preferably have a length of up to 5 μm, for example 4 to 5 μm.
[0050] Preferably, the grains of the first and second deposits having a smaller grain size before the conversion step are almost completely (meaning more than 90% of the smaller grain size) converted into the larger grain size of the connected deposit, and the larger grain size passes through the connected deposit.
[0051] Preferably, the connected and transformed deposit has no, or at least partially no, detectable joint surface (interface) between the original first deposit and the original second deposit: the original uniform and smooth surface is at least partially invisible after transformation, for example under a FIB SEM microscope.
[0052] In one embodiment, the grains of the first and second deposits having a smaller grain size are almost completely (meaning more than 90% of the smaller grain size) converted into larger grain size grains of the connected deposit, the larger grain size grains passing through the connected deposit, and the connected deposit has no detectable joining surface (interface) between the original first deposit and the original second deposit after the conversion step d).
[0053] In the context of the present invention, the absence of a detectable joining surface (interface of both joined surfaces after transformation) between the original first deposit and the original second deposit means that after steps a), b) or c), the joining surface present in the first and second deposits before carrying out step d) can no longer be detected as a smooth / uniform surface. This is because the grain size of each deposit grows from nanocrystalline size to a grain size of 0.1 μm to 13 μm on average, thereby penetrating into the other deposit. In other words, the joining surface, or at least a part of the joining surface (also called the interface between these joining surfaces), can no longer be detected as belonging to the original deposit. Instead, the original distinct surface or at least a part of the surface merges into the other. This is in contrast to the prior art, where deposits are used (for example shown in the comparative example) whose grain size cannot grow or whose grain size has already been transformed before the joining or transformation step.
[0054] No "detectable" joining surface (interface) in this context means that the joining surface of the original copper deposit in step d), or at least a part of the surface (having a homogeneous tendency), after the conversion in step d) is not visible or partially not visible / observable as belonging to the original deposit by known methods such as EBSD (Electron Backscatter Diffraction) or FIB SEM microscopy.
[0055] The conversion step d) is carried out by applying an annealing step having an annealing temperature below 200° C., preferably between 150° C. and 200° C., more preferably between 150° C. and less than 200° C. Preferably, the annealing time is between 10 min and 90 min.
[0056] In the case of the D2W or D2D process, the annealing time is preferably 45 minutes to 75 minutes, most preferably 60 minutes, and the annealing temperature is preferably 150° C. to 200° C., more preferably 150° C. to less than 200° C. In the case of the W2W process, the annealing time is preferably 10 minutes to 20 minutes, and the annealing temperature is preferably 150° C. to 200° C., more preferably 150° C. to less than 200° C.
[0057] In another embodiment, step c) is carried out together with step d), and the temperature used in step c) is the annealing temperature of step d). In this embodiment, the connecting and converting steps are carried out simultaneously by applying an annealing step having an annealing temperature of 200°C or less, more preferably 150°C to 200°C, and most preferably less than 150°C to 200°C. In this embodiment, the first deposit and the second deposit undergo thermal expansion, and the copper grains of the first deposit and the copper grains of the second deposit also begin to convert and spread, respectively, so that the joining surfaces of the first deposit and the joining surfaces of the second deposit come into contact with each other, so that the grown copper grains of the first and second deposits finally come into contact with each other, intercalate, and form a connected and converted deposit. In a special embodiment, the temperature is increased stepwise to the above-mentioned annealing temperature.
[0058] The thermal expansion may be supported by additional metal deposits on the first and second substrates, attached to the first and second deposits on the opposite side of the joining surface (but not attached to the joining surface). The additional metal deposits may have more than one metal composition, for example a copper alloy. Each additional metal deposit also has a respective coefficient of thermal expansion (COE). This also mitigates the connection step c) so that the joining surfaces of the first and second deposits come into contact.
[0059] Preferably, the method of the present invention is a direct hybrid bonding method, in which the first substrate further comprises a first non-conductive material, e.g. a dielectric material having a bonding surface and at least partially encapsulating the first deposit, and the second substrate further comprises a second non-conductive material, e.g. a dielectric material having a bonding surface and at least partially encapsulating the second deposit, where the bonding surfaces of the first and second deposits are below or equal to the plane of the bonding surfaces of the first and second non-conductive materials. In this embodiment, the bonding surfaces of the non-conductive materials are first connected (if the bonding surfaces of the first and second deposits are below) by placing at least a part of the bonding surfaces of the non-conductive materials of the substrates in direct contact with each other, e.g. by arranging the substrates face to face and clamping them together on a bonding chuck under conditions as described above, and then the bonding of the bonding surfaces of the deposits and step d) are performed. If the bonding surfaces of the first and second deposits are at the same height relative to the bonding surfaces of the non-conductive materials, both bonding steps (connecting steps) are performed simultaneously. Preferably, steps c) and d) are carried out together, where during the connection the joining surfaces of the substrates (of the non-conductive material and the deposit) are heated from room temperature to the above-mentioned annealing temperature. By heating, step d) is carried out almost simultaneously or is started when the annealing temperature is reached. In principle, the process flow of direct hybrid bonding comprises two joining steps in step c), after electrolytic copper deposition, CMP and thus a first joining of the dielectric material and a second or simultaneous joining of the first and second deposits. Such hybrid bonding methods are in principle known to the skilled person and are described, for example, in WO2020046677A1. The non-conductive material can be a material based on polymers such as SiO2, SiCN, SiN or polyimide (PI). Since the copper deposit was formed in an electrochemical copper deposition step, the joining surface of the metal deposit is already very smooth (preferably with a surface roughness Ra of 10 nm to 30 nm). However, if a surface roughness Ra of less than 10 nm is required and / or cleaning is required, a short CMP step may be useful.
[0060] Alternatively, step c) can be carried out without heating to a higher temperature, in particular at a temperature below 100° C., preferably at room temperature (preferably in the range 18-25° C.), with step d) preferably being carried out as the immediate subsequent step.
[0061] The aqueous copper electrochemical deposition bath may be any bath that results in first and second pure copper deposits having small grain sizes, preferably nanocrystalline copper grains. The aqueous acid copper plating bath is operated in the method according to the invention by applying an electric current to the substrate and to at least one anode, preferably at a temperature range of 15°C to 40°C, more preferably at a temperature range of 20°C to 35°C.
[0062] As explained at the beginning, the most important point of the present invention is that the small grain size of the first and second deposits must be maintained until step d) of the method of the present invention is started. Preferably, after the electrochemical copper deposition step of preparing the first and second copper deposits, and before the conversion in step d), no other conversion step that may change the grain size of the copper grains of the first and second deposits is performed, and preferably no annealing step or any other step including heating is performed, for example, no annealing step having an annealing temperature of more than 100°C is performed, and preferably no annealing step at 100°C to 200°C for 1 hour is performed. Preferably, the period after steps a) and b) until steps c) and / or d) are performed does not exceed 3 weeks, more preferably does not exceed 120 hours, and even more preferably does not exceed 72 hours. Preferably, the substrate from steps a) and b) is stored at room temperature (in the range of 18°C to 25°C), preferably below 25°C, more preferably in the range of 5°C to 25°C, during the above period.
[0063] Furthermore, surface modification of the joining surfaces of the first and second deposits by additional treatment steps to roughen the joining surfaces after the electrochemical copper deposition step and / or before the connecting step c) is not required by the present invention and therefore does not apply to the method of the present invention and is excluded from the method of the present invention. In particular, the joining surfaces of the first and second deposits have smooth surfaces without generated nanotextured structures. These additional structures result in a surface roughness Ra of several hundred nanometers. In other words, no nanostructured surfaces are formed on the joining surfaces of the first and second deposits, for example by pickling with very dilute acids, etching, polishing or other methods, as nanotextured surfaces in the copper surface.
[0064] However, if necessary, the surface roughness of the bonding surface after steps a) and / or b) can be further reduced by CMP (Chemical Mechanical Polishing). A shorter CMP time can be used to clean the bonding surface.
[0065] The electrochemical copper deposition step can be part of a process of preparing structures on the first and second substrates in the form of a first deposit and a second deposit, the first and second deposits being independently selected from the group consisting of vias, bumps, pillars and / or pads. In principle, therefore, any electrochemical copper deposition process can be used, as long as it results in a good filling performance of the structures to be filled and in a preferably smooth joining surface of the first and second deposits. The process of preparing structures is in principle known to the person skilled in the art and can be, for example, a damascene process, a process of filling a structured resist with copper, etc.
[0066] The electrochemical copper deposition process preferably includes using an aqueous acidic copper electrolytic bath containing a copper ion source, a sulfur-containing brightener compound, a suppressor compound, a leveller selected from the group consisting of a guanidine-containing compound, a urea-containing compound, an imidazole-containing compound and a pyridine-containing compound, and a halide ion. The bath preferably has a pH value of less than 2, more preferably less than 1. All compounds can be purchased commercially from Atotech Deutschland GmbH.
[0067] The copper ion source is preferably selected from the group consisting of copper sulfate and copper alkylsulfonates such as copper methanesulfonate. The copper ion concentration in the aqueous acid copper plating bath is preferably in the range of 4 g / L to 90 g / L, more preferably 10 g / L to 70 g / L, and even more preferably 30 g / L to 65 g / L.
[0068] The acid is preferably selected from the group including sulfuric acid, fluoroboric acid, phosphoric acid, and methanesulfonic acid, and is added at a concentration of preferably 10 g / L to 400 g / L, more preferably 20 g / L to 300 g / L, and even more preferably 30 g / L to 300 g / L.
[0069] The sulfur-containing brightener compound is preferably selected from the group consisting of 3-(benzthiazolyl-2-thio)-propylsulfonic acid, 3-mercaptopropane-1-sulfonic acid, ethylenedithiodi-propylsulfonic acid, 3-N,N-dimethylaminodithiocarbamoyl-1-propanesulfonic acid, and 3,3'-dithiobis-1-propanesulfonic acid (SPS) or a salt thereof, preferably dithiobis-1-propanesulfonic acid (SPS). The (total) concentration of all accelerator-brightener additives optionally present in the aqueous acidic copper bath composition is preferably in the range of 0.01 mg / L to 100 mg / L, more preferably in the range of 0.05 mg / L to 20 mg / L, and even more preferably in the range of 0.1 to 10 mg / L.
[0070] The suppressor compound is preferably selected from the group consisting of polyethylene glycol (PEG), polypropylene glycol, poly(ethylene glycol-lan-propylene glycol), polyethylene glycol / polypropylene glycol-copolymer, poly(ethylene glycol)-block-poly(propylene glycol)-block-poly-(ethylene glycol), and poly(propylene glycol)-block-poly(ethylene glycol)-block-poly(propylene glycol), preferably polyethylene glycol or polyethylene glycol / polypropylene glycol-copolymer (PEG / PPG). Preferably, the molecular weight (MW [g / mol]) of the suppressor is 4,000 to 8,000. The (total) concentration of the optional carrier-suppressor additive is preferably in the range of 0.005 g / L to 20 g / L, more preferably 0.01 g / L to 20 g / L, and even more preferably 0.01 g / L to 5 g / L.
[0071] The guanidine-containing compound is a polymeric compound having repeating units of a guanidine residue and a divalent residue. Examples thereof are disclosed in EP3286358B1, which is incorporated by reference, and can be purchased from Atotech Deutschland GmbH. The concentration of the guanidine compound in the aqueous acid copper plating bath is in the range of 0.01 mg / L to 1000 mg / L, more preferably 0.1 mg / L to 100 mg / L, and even more preferably 0.5 mg / L to 50 mg / L.
[0072] The halide ion is preferably selected from Cl, Br, and / or I. In the case of chloride, the halide ion is added in a concentration range of preferably 10 to 200 mg / L, more preferably 20 to 80 mg / L, and even more preferably 30 to 60 mg / L. When another type of halide ion is selected, the molar amount of each is preferably selected, and when different halides are selected, the total molar amount of each is selected.
[0073] Preferably, the electrochemical copper deposition step is performed by applying a current density of 1-2 ASD to obtain the first and second deposits, and direct current (DC) plating and pulse plating can be used. In one embodiment, the electrochemical copper deposition step is performed by pulse plating, for example, forward and reverse pulses, or forward and off pulses of current and time.
[0074] The invention will now be described with reference to the following figures and non-limiting examples. EXAMPLES
[0075] FIG. 1 shows the formation of a copper-copper direct bond according to the prior art (a) and a copper-copper direct bond according to the present invention (b).
[0076] It is known that electrochemically deposited copper according to the prior art also consists of fine grains initially after deposition, but easily recrystallizes into larger grains depending on temperature and time. Grains that do not grow further are thought to lead to the formation of an interface between the joining components (Figure 1a). In contrast, when joining is performed with grain sizes close to the initial state after deposition, grain growth is observed on the joining surfaces (interfaces) of the first and second deposits, while the interface disappears (Figure 1b).
[0077] The following Figures 2 to 4 support the findings in Figure 1, which can be applied to copper-copper direct bonding and lead to improved bonding strength and electrical conductivity.
[0078] Figure 2 simulates the conversion step d) of the invention, where one copper layer (first deposit) is annealed. Figure 2 shows the effect of the annealing temperature over time on the average grain size in 4.5 μm thick copper deposits (with about 2,500 ppm organic impurities on the substrate (comparative example) and pure copper deposit on the substrate (example of the invention)) after applying an annealing step of 1 hour at different temperatures.
[0079] The annealing temperature of the copper deposit can be tuned by the co-deposition of other elements, both inorganic and organic. Co-deposition of inorganic elements, especially other metals, results in the formation of alloys, which reduces the electrical conductivity compared to pure copper. Organic impurities are usually due to the co-deposition of organic plating additives. It has been shown that a fairly pure deposit can be obtained by properly designing the additives. This technique was utilized to reduce the temperature required for annealing the copper material. The grain size of the various layers produced by electrolytic deposition was measured by EBSD after annealing at different temperatures for 1 h (Figure 2a). The deposit produced from electrolyte 1 required significantly higher temperatures to obtain the final grain size compared to electrolyte 2. Both electrolytes had similar grain sizes after annealing at high temperatures, on the order of the deposit thickness (4.5 μm). The amount of each of the co-deposited impurities was measured by dynamic secondary ion mass spectrometry (DSIMS) and confirmed to be higher for electrolyte 1 (Table 1 below). Differential scanning calorimetry (DSC) confirmed an exothermic peak, further supporting the idea that copper with high impurity content requires high temperatures for crystallization (Table 1 below). Electrolyte 1 was based on conventional organic plating additives that tend to lead to significant codeposition, while electrolyte 2 was composed of optimized additives, which allowed for a high-purity final layer.
[0080] It was argued that the upper limit for copper-copper joint formation in hybrid joining applications is 200 °C. Therefore, the copper material should reach its maximum grain size at such a temperature. Figure 2a shows that the deposits from both electrolytes eventually reach a grain size of about 3.5 μm, close to the thickness of the deposit. However, for electrolyte 1, temperatures above 300 °C are required. In contrast, electrolyte 2 produces copper that reaches its maximum grain size at a temperature of about 200 °C. The average grain size, including twins, at 200 °C reached a maximum within the margin of error for electrolyte 1, but remained at a value of 1.1 μm even at 230 °C. The corresponding EBDS image is shown in Figure 2b. A comparison of the grain sizes of electrolytes 1 and 2 in this temperature range confirmed the suitability of electrolyte 2.
[0081] Figure 2a shows the average grain size including twins of 4.5 μm thick copper deposits obtained from electrolyte 1 (grey) and electrolyte 2 (black) directly measured by EBSD after annealing at different temperatures for 1 h (top). Corresponding examples of EBSD images for electrolyte 2 after annealing at 110 °C and 400 °C for 1 h, respectively (bottom).
[0082] Figure 2b shows direct EBSD images of 4.5 μm thick copper deposits obtained from electrolyte 1 (top) and electrolyte 2 (bottom) after annealing at 230 °C for 1 h.
[0083] The deposits made from electrolyte 1 (Comparative Example - (Comp.Ex)) required significantly higher temperatures to achieve the final grain size compared to electrolyte 2 (Inventive Example 1 - (Inv.Ex1)). Both electrolytes had similar grain sizes after annealing at high temperatures, on the order of deposit thickness (4.5 μm). The amount of each of the codeposited impurities was measured by dynamic secondary ion mass spectrometry (DSIMS) and found to be higher for electrolyte 1 (Table 1). Differential scanning calorimetry (DSC) showed an exothermic peak, further supporting the need for high temperatures for crystallization of copper with high impurity content (Table 1). While electrolyte 1 was based on conventional plating organic additives that tend to exhibit significant codeposition, electrolyte 2 was composed of optimized additives, which allowed for a high purity final layer.
[0084] [Table 1]
[0085] Electrolyte 1 (Comp.Ex): Sulfur-containing brightener SPS 2mg / L Suppressor compound PEG (MW 6000) 300mg / L Leveler PEI (MW 600) 0.1mg / L Deposition at 5ASD, temperature 25℃ Annealed at over 200°C after deposition Electrolyte 2 (Inv.Ex): Sulfur-containing brightener SPS 4mg / L Suppressor compound PEG / PPG copolymer (MW 6000) 10mL / L Guanidine-containing compound: Atotech (registered trademark) Spherolyte Leveler DB 20mL / L Deposition with 1ASD, temperature 25℃ After deposition in step d), anneal at 200° C. for 1 hour.
[0086] Figure 3 shows the normalized grain size of copper alloy (comparative) and pure copper deposits (inventive example) where one copper layer (first deposit) was investigated over time at room temperature. Figure 3 shows the normalized grain size of deposits made from electrolyte 2 using parameter sets 1 (5ASD DC, 25°C) (grey) and 2 (1ASD DC, 25°C) (black) as a function of time at room temperature (top). Examples of the corresponding microstructures immediately after deposition (left), after 12 hours (middle) and after 24 hours (right).
[0087] All process steps prior to step d), in particular the deposition process itself, the connection step c) and for example the CMP process, are carried out at room temperature (ambient temperature) or below, thus making it necessary to maintain a morphology similar to the initial structure after deposition for as long as possible and to ensure sufficient time to carry out all necessary process steps prior to the copper-copper bonding of step d) at high temperature.
[0088] To investigate the timescale of the microstructural evolution, the grain size of deposits made from electrolyte 2 (mentioned above) was measured after different times at room temperature (Figure 3). Grain growth at room temperature is usually called self-annealing. The time until the maximum grain size is obtained can be varied by the process parameters of the electrolytic deposition. Using parameter 1, the maximum grain size was obtained after about 9 hours. This time may not be sufficient for implementation in a production sequence. In contrast, deposits made using parameter 2 required more than 24 hours at room temperature before no further grain growth was observed. This time is much longer and therefore more suitable for current industrial production process flows.
[0089] The deposit transformation during the joining process was simulated and investigated over time for different deposits at different temperatures in Figure 4. Figure 4 shows FIB SEM micrographs of pure copper deposits deposited with different parameters of time and temperature, here FIB SEM micrographs of copper deposited from electrolyte 2 with parameters 2 (1ASD DC, 25 °C) are shown as follows: Figure 4a) 4.5 μm monolayer after deposition (simulating a first deposition on a first substrate). Figure 4b) A 4.5 μm monolayer after 24 h at room temperature (simulating a first deposition on a first substrate). FIG. 4c) Two successively deposited 4.5 μm layers after annealing at 200° C. for 1 hour, the second layer being deposited after self-annealing of the first layer at room temperature for 24 hours (simulating the conversion of a first deposit on a first substrate and a second deposit on a second substrate according to a non-inventive example). FIG. 4d) Two successively deposited 4.5 μm layers, the second one deposited directly after the deposition of the first, after annealing at 200° C. for 1 hour (simulating the conversion of a first deposit on a first substrate and a second deposit on a second substrate according to the invention).
[0090] The ability of deposits with small grain initial microstructure to grow further through the interface (attached joint surface of the first and second deposits) was investigated by two successive electrochemical deposition steps with different annealing conditions in between. A first deposit with a thickness of 4.5 μm was made from electrolyte 2 with process parameters 2, which initially showed small grains (Figure 4a), which grew considerably within 24 hours at room temperature as it self-annealed (Figure 4b). A second electrochemical deposition step under the same conditions was performed on the initial and self-annealed microstructures. After the deposition of the two layers, the whole stack was annealed at 200 °C for 1 hour to approximate the thermal load conditions during copper-copper bonding. When the second layer was deposited on the first layer after self-annealing, an interface was observed after annealing (Figure 4c - not invented). In contrast, when the second layer was deposited on the first layer that still had the initial microstructure, no interface or grain growth was detected throughout the deposit consisting of two successively deposited layers (Figure 4d).
[0091] FIG. 5 shows FIB SEM micrographs of the formation of copper-copper direct bonds in wafer pairs according to the invention and a comparative example.
[0092] Four 300 mm DBI5 wafers were prepared according to steps a) and b) of the present invention as two first substrates and two second substrates, the first substrate having a bonding surface and further comprising a first non-conductive material encapsulating the first deposit, and the second substrate having a bonding surface and further comprising a second non-conductive material encapsulating the second deposit. Both substrates are made of the same non-conductive material, and the first and second copper deposits are formed by the same electrochemical copper deposition process. The electrochemical copper deposition process was performed using electrolyte 2 (Invention Example 1 - (Inv.Ex1)). All steps were performed within 24 hours.
[0093] Examples of the present invention After 60 minutes of electrochemical copper deposition, the two wafers (first and second substrates) were treated with a short CMP step. As explained in the overview, the CMP step was performed for a short time mainly to clean the surface of the copper deposit. However, it was possible to reduce the polishing time and waste. Afterwards, the two wafers were bonded at ambient temperature (step c) and annealed for 60 minutes at less than 200 °C according to step d).
[0094] FIG. 5a shows a FIB SEM micrograph of the resulting Cu-Cu bonded wafer pair, with a magnitude of 2k.
[0095] The photographs show that the connected and transformed deposits are formed by the passage of grains through the first deposit into the second deposit, and vice versa, and that the distinct interface between the first and second deposits does not disappear, but at least partially disappears from the viewer.
[0096] FIG. 5b shows another FIB SEM micrograph of the copper-copper bonded wafer pair rotated 90 degrees from FIG. 5a at 20k magnification, and FIG. 5c shows a FIB SEM micrograph of the same wafer pair at 50k magnification.
[0097] It can be seen that the converted deposit has no clearly detectable joint surface (interface) between the original first deposit and the original second deposit, which means that during the conversion step d) the grain size grows and the formed copper grains pass through the joint surface of the first and second deposits and spread into the respective other deposit.
[0098] Comparative Example 60 minutes after the electrolytic copper deposition, the wafers (first and second substrates) were subjected to an annealing step at 200°C for 60 minutes to force grain growth by heat treatment. After this step, the two wafers (first and second substrates) were subjected to a short CMP step. The two wafers were then bonded and annealed again at 200°C for 60 minutes according to steps c) and d).
[0099] FIG. 6a shows a FIB SEM micrograph of the resulting Cu-Cu bonded wafer pair, with a size of 2k.
[0100] The connected deposits that are formed show a clearly visible interface between the first and second deposits, with no portions of the surface of the deposit fused to the surface of the other deposit.
[0101] FIG. 6b shows another FIB SEM micrograph of the copper-copper bonded wafer pair at a magnification of 20k, rotated 90 degrees from FIG. 6a, and FIG. 6c shows a FIB SEM micrograph of the same wafer pair at a magnification of 50k.
[0102] It can be seen that the formed deposit has a visible joining surface (interface) between the original first deposit and the original second deposit, and that the grown grains do not penetrate into the joining surface of the deposits, in other words, there are no grains extending across the entire area of the first and second deposits.
[0103] This means that during the first heat treatment (first annealing step before step c) the transformation took place and was completed in each deposit (first and second deposit). The further annealing step in step d) could not initiate further grain size growth. In particular, the grain size did not increase any more and the copper grains did not spread through the joining surface of the first and second deposits into the other deposit, since the grain size growth was already completed during the first annealing step.
Claims
1. 1. A method for copper-to-copper direct bonding comprising: a) providing a first substrate having a bonding surface and comprising a first copper deposit having a copper content of at least 99% by weight, preferably said first substrate being a wafer or die-like substrate; b) providing a second substrate having a bonding surface and a second copper deposit having a copper content of at least 99% by weight, preferably said second substrate being a wafer-like substrate or a die-like substrate; c) connecting the mating surfaces of the first and second deposits by applying pressure with a contact force of 1-5,000 N to obtain a connected deposit; d) transforming the first and second stacks of the connected stack into a connected and transformed stack; Including, - the first deposit and the second deposit are formed by an electrochemical copper deposition step and have copper grains with a smaller grain size than the grain size after conversion in step d), preferably the grain size is less than 1 μm, - said connected and converted deposits have grains with a size larger than the grains of said first and second deposits before conversion in step d), preferably said grains being between 0.1 μm and 13 μm, more preferably between 1 and 10 μm, said step d) being carried out by applying an annealing step having an annealing temperature below 200° C., preferably between 150° C. and 200° C., The method of claim 1, wherein grains of the first and second deposits having a smaller grain size are converted to larger grains of the connected deposits by more than 90% of the smaller grain size, and the larger grains pass through the connected deposits.
2. The method of claim 1, wherein the annealing step is carried out for a time period between 10 minutes and 90 minutes.
3. The method according to claim 1 or 2, wherein the joining surfaces of the first and second deposits have a surface roughness Ra of less than 200 nm, preferably in the range of 5 nm to 200 nm.
4. 4. The method according to claim 1, wherein the connected deposits have no or at least partially no detectable joining surface (interface) between the original first deposit and the original second deposit after conversion step d) in a 2k, 20k or 50k FIB SEM microscope.
5. 5. The method according to claim 1, wherein after the electrochemical copper deposition step and before the connection of step c), no conversion step is carried out which changes the grain size of the copper grains of the first deposit and of the second deposit, and preferably no annealing step is carried out having an annealing temperature above 100°C, preferably between 100°C and 200°C.
6. 6. The method of claim 1, wherein the method is a direct hybrid bonding method, the first substrate further comprising a first non-conductive material having a bonding surface and at least partially encapsulating the first deposit, the second substrate further comprising a second non-conductive material having a bonding surface and at least partially encapsulating the second deposit, and the bonding surfaces of the first and second deposits are below a surface of the bonding surfaces of the first and second non-conductive materials.
7. 7. The method of any one of claims 1 to 6, wherein the electrochemical copper deposition step comprises the use of an aqueous acid copper deposition bath operated in the temperature range of 15°C to 40°C.
8. 8. The method of any one of claims 1 to 7, wherein the electrochemical copper deposition step comprises using an acidic copper deposition bath comprising a copper ion source, a sulfur-containing brightener compound, a suppressor compound, a leveler selected from the group consisting of a guanidine-containing compound, a urea-containing compound, an imidazole-containing compound, and a pyridine-containing compound, and halide ions.
9. 9. The method according to any one of claims 1 to 8, wherein the electrochemical copper deposition step is carried out by applying a current density of 1 to 2 ASD to obtain the first and / or second deposit.
10. 10. The method according to claim 1, wherein the joining surface of the first deposit and the joining surface of the second deposit have a smooth surface, preferably without a nano-textured structure, the smooth surface having a surface roughness Ra of less than 200 nm, preferably less than 50 nm.
11. 11. The method according to claim 1, wherein after the electrochemical copper deposition step and / or before the connecting step c) no surface modification of the joining surfaces of the first and second deposits is applied.
12. i) An assembly comprising a connected and transformed deposit, the deposit comprising: - connecting a joining surface of a first copper deposit of a first substrate, the first copper deposit having a copper content of at least 99% by weight, with a second joining surface of a second copper deposit of a second substrate, the second copper deposit having a copper content of at least 99% by weight, by applying a contact force of 1 to 5,000 N; - transforming said first and second piles of connected piles into a connected and transformed pile. is obtained by - the first and second deposits are formed by an electrochemical copper deposition process and have copper grains with a smaller grain size compared to the copper grains of the connected and converted deposits with a larger grain size after applying an annealing process with an annealing temperature of less than or equal to 200°C, preferably between 150°C and 200°C, the grains of the first and second deposits with a smaller grain size are transformed by more than 90% of the smaller grain size into the grains of the larger grain size of the connected deposit, the grains of the larger grain size passing through the connected deposit, assembly.
13. i) a device comprising an assembly comprising a connected and transformed deposit, the deposit comprising: - connecting a joining surface of a first copper deposit of a first substrate, the first copper deposit having a copper content of at least 99% by weight, with a second joining surface of a second copper deposit of a second substrate, the second copper deposit having a copper content of at least 99% by weight, by applying a contact force of 1 to 5,000 N; - transforming said first and second piles of connected piles into a connected and transformed pile. is obtained by - the first deposit and the second deposit are formed by an electrochemical copper deposition process and have copper grains with a smaller grain size compared to the copper grains of said connected and converted deposits with a larger grain size after applying an annealing step with an annealing temperature of less than or equal to 200°C, preferably between 150°C and 200°C, - the grains of the first and second deposits having a smaller grain size are converted by more than 90% of the smaller grain size into the larger grain size of the connected deposits, the larger grain size passing through the connected deposits; A device, wherein the first and second substrates are part of a microelectronic device, preferably a wafer or a die.